Anxiety and depression in inflammatory bowel disease: a systematic review and meta-analysis of prevalence, incident risk, and disease subtype differences - Roshan Mustafa Pathan; Saahi Ghanta; Ponni Gayatri Twinkle Bade; Mukesh Ram Kumar Kommu; Vamsi Krishna Kondepati; Naga Keerthi Gangavarapu; Lakshmi Teja Navuluri; Sikendra Teja Munipally; Prerana Lakkakula (The Egyptian Journal of Internal Medicine, 2026)
Abstract Purpose Extraintestinal manifestations of inflammatory bowel disease (IBD) include anxiety and depression, with estimates varying across IBD types. We conducted a review and meta-analysis to estimate prevalence and incidence of anxiety and depression in IBD, compare psychiatric burden in Crohn’s disease (CD) and ulcerative colitis (UC), and identify heterogeneity. Methods MEDLINE (PubMed) and Embase were searched for anxiety/depression in IBD until May 2026. Random-effects meta-analyses calculated pooled prevalence/risk; heterogeneity was evaluated through Cochran’s Q, I², τ², and meta-regression. PROSPERO ID CRD420261297050. Results Twenty-two studies were included in the analysis. Thirteen studies ( n = 5,616) reported an anxiety prevalence of 24% (95% CI, 19–30%), and 15 studies ( n = 5,956) reported a depression prevalence of 24% (95% CI, 20–28%). Six cohort studies showed that IBD was associated with increased anxiety (HR 1.36, 95% CI, 1.17–1.59) and depression risk (HR 1.44, 95% CI, 1.35–1.54) versus non-IBD controls. No differences were observed between CD and UC for anxiety (OR 1.05, 95% CI, 0.64–1.73) or depression (OR 1.13, 95% CI, 0.86–1.48). Region explained heterogeneity, and instruments did not influence the estimates. The findings were robust, and no publication bias was identified. Conclusions One in four with inflammatory bowel disease (IBD) experiences anxiety or depression, and Crohn’s disease (CD) and ulcerative colitis (UC) burden suggest inflammation underlies this risk. Findings support assessment, clarify gut-brain links, and identify beneficiaries.